Pancreatic Metastasis of Renal Cell Carcinoma: A Surgical Indication for a Disseminated Disease - Feryel Letaief Ksontini; Salim Khrouf; Selma Kacem; Anis Haddad; Houcine Magherbi; Youssef Chaker; Mouna Ayadi; Zoubair Ben Safta (Case Reports in Medicine)
Pancreatic metastasis (PM) of renal cancer is a rare condition. It is characterized by a long period after initial nephrectomy and a favorable prognosis compared to other pancreatic malignancies. Its diagnosis may confuse clinicians if the medical history is not known. In the era of targeted therapies for metastatic renal carcinoma, surgery stands as the best treatment option for PM of renal cancer. We report the case of a woman who underwent successfully left splenopancreatectomy for corporeal PM of renal cancer treated seven years ago. This case underlines the necessity of long-term follow-up of patients treated for kidney cancer.